Photoinduced Antifungal Studies Of Carbon Nanoparticle And Functionally Modified Hyperbranched Polyglycerol-Carbon Nanoparticle Aggregates (Journal of Namibian Studies : History Politics Culture, 2023)
This paper describes the synthesis of carbon nanoparticle (CNP) from natural sources such as kitchen soot, synthesis of a chromophoric system {5-[4-(dimethylamino) benzylidene]-4-oxo-2-thioxo1, 3-thiazolidin-3-yl} acetic acid and its incorporation into  hyperbranched polyglycerol (HPG) through the esterification of the hydroxyl group with the free carboxyl function of the chromophoric system by DCC coupling, encapsulation of CNP in to functionally modified HPG system, characterization of the products by  UV-visible, FT-IR, NMR, fluorescence spectroscopic methods, scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray diffraction (XRD) methods, and  study of their antifungal action. The antifungal activity of CNP and functionally modified HPG-CNP aggregates were tested against various pathogenic fungal strains such as Aspergillus niger, Aspergillus fumigates, Aspergillus flavus, Penicillium janthinellum, and Mucor ramosissimus by well diffusion method.  The results proved that the CNPs and functionally modified product have excellent antifungal activity against selected pathogenic fungal strains.